The therapeutic potential of plant extraction in oral health - a systematic review / Faziatul Amirah Mohd Fauzi ... [et al.] - Mohd Fauzi, Faziatul Amirah; Mischon, Abigail Michelle; Zain, Nurhayati Mohamad; Baharuddin, Izyan Hazwani (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Objectives: This study aimed to analyze the therapeutic potential of plant extract against oral microorganisms in published literature. Material and Method: A systematic literature review was performed through electronic databases (Scopus, EBSCO: Dentistry and Oral Science Source) from January 2009 till December 2019 with the search terms ("extract" AND ("ORAL MICROORGANISM" OR "ORAL BACTERIA") AND ("stem" OR "Bark" OR "Leaf")). Results: Out of 409 articles, 21 articles met our inclusion criteria that were subjected to data extraction and review. The data disclosed antimicrobial and antibiofilm activity of plant extracts against causative microorganisms of caries, periodontitis, endodontic infection, and fungal infection. Ethanol was the most common solvent used for plant extraction. The antimicrobial test was reported in all studies using different methodologies such as minimum inhibitory concentration (MIC), disk diffusion method, agar well method, intracanal irrigation, and Fractional Inhibitory Concentration Index (FICI) . None of the plant extract tested showed significant toxicity in five studies that conducted toxicity assays. Conclusion: A positive correlation was observed between plant extract and antimicrobial activity against oral microorganisms. In that context, integrating plant extract in oral healthcare products could be an option to enhance effective antimicrobial control. However, further clinical studies are required to provide clinical evidence to support these observations.